Hydrogen and methane production from palm oil mill effluent through two-stage dark fermentation - Santhana, Krishnan Chandrasekar (2017)
Two-stage dark fermentation is a green technology, presents an outstanding opportunity for both high energy conversion and pollution control. The main objective of this research is to investigate two-stage dark fermentation processes for sequential hydrogen (H2) and methane (CH4) production using palm oil mill effluent (POME) in up-flow anaerobic sludge blanket–continuous stirred tank reactor (UASB-CSTR). During the experiment, H2 was produced in UASB reactor at thermophilic condition (55ºC) in the first stage, while CH4 was produced from the effluents of UASB reactor in the CSTR at mesophilic condition (37ºC) in the second stage. The heat treated and non-heat treated anaerobic sludge was used as inoculum for UASB and CSTR reactor, respectively. In the first study, batch test was conducted to find out the hydrogen production potential (HPP) and methane production potential (MPP) of POME. Following, the UASB reactor operated continuously at thermophilic conditions with the hydraulic retention time (HRT) of 2 days and organic loading rate (OLR) 75 kgCOD m3ˑd-1 for H2 production. The effluents from UASB reactor were directly fed into CSTR for CH4 production at mesophilic temperature with the HRT of 5 days. The maximum H2 and CH4 production rate achieved was 1.92 L H2 L-1d-1 and 3.2 L CH4 L-1 d-1, respectively. The cumulative H2 and CH4 yields were 215 L H2/kgCOD-1 and 320 L CH4/kgCOD-1, respectively with the total COD removal efficiency of 94%. The sludge granules from both UASB and CSTR reactor were analyzed using scanning electron microscopy and the microbial community was analyzed using polymerase chain reaction denaturing gradient gel electrophoresis (PCR-DGGE). Results revealed that sludge granules were nearly round shaped with multiple cracks on the surface and UASB and CSTR reactor was enriched with Thermoanaerobacterium species and Methanobrevibacter species, Methanosarcina species, repectively. The second study addressed the effect of recirculation of methane effluent into UASB reactor for the continuous H2 and CH4 production. HPP from POME mixed with methanogenic effluent at recirculation rate of 50%, 40%, 35%, 30%, 20% and 10% was investigated. The recirculation of methanogenic effluent at 35% recirculation rate could compensate for alkalinity required by UASB reactor. The maximum H2 and CH4 yield were 178 mL H2/gCOD and 412 mL CH4/gCOD, respectively. Two-stage process with methanogenic effluent recirculation flavoured the UASB reactor and efficiently for energy recovery from POME. In the third study, influence of different organic loading rates (OLR) such as 25, 50, 75, 100, 125 kg-COD/m3∙d was analyzed for the improvement of hydrogen and methane production rate and yield. The better yield was achieved when the OLR was in the range of 75 kg-COD/m3∙d. The maximum H2 production rate was 175.15 mL H2/g MLVSS∙d, while the highest H2 content and yield were 35% and 49.22 mL H2/g CODapplied, respectively. The maximum CH4 content, CH4 yield, and specific methane production rate (SMPR) were 68%, 155.87 mL CH4/g CODapplied and 325.13 mL CH4/g MLVSS∙d, respectively. The results indicated that OLR affected H2-CH4 production and substrate removal efficiency. Finally, the studies on the influence of flow rate (QF) and up-flow velocity (Vup) ranging (1.7-10.2 L/d) and (0.5-3.0 m/h), respectively on hydrogen production using response surface methodology (RSM) showed that H2 yield was 0.32 L H2 g-1 COD at QF and Vup of 1.7 L d-1 and 0.5 m h-1, respectively The optimum ranges for the fermentative hydrogen production of the POME were QF = 2.1-3.7 L/d and Vup =1.5-2.3 m/h. The experimental results agreed very well with the model prediction.